Thelma [videorecording (DVD)] - Trier, Joachim; Harboe, Eili, 1994-; Wilkins, Kaya; Rafaelsen, Henrik, 1973- ([Passion River Films], 2018)
A shy young student leaves her small town and religious family to study at a university in Oslo, but once on campus she experiences what appears to be a violent, unexpected seizure. Overwhelmed by the increasing intensity of the mystifying episodes and her powerful feelings for a beautiful classmate, she struggles to control her supernatural abilities.